Development and study of iron-based nanoadsorbents - Deliyanni E.; Bakoyannakis D.; Zouboulis A.; Matis K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The application of an innovative, simple and low cost method was tested for the preparation of nanocrystalline iron hydroxides and oxyhydroxides; different iron precursors have been earlier used and combined to different volatile precipitating agents. The examined in the present product, akaganéite [â-FeO(OH)], had high surface area and definite pore size distribution. The produced materials were examined in detail (i.e. by powder X-ray diffraction, TEM and nitrogen sorption measurement). Main aim of this study was to evaluate the efficiency of the prepared material in the removal of heavy and toxic metal cations, like Cd(II), from aqueous solutions; cadmium constitutes a priority pollutant. Sorption was found to depended on the solution pH and its ionic strength. Typical isotherm models were applied and calculated the values of maximum adsorbent capacity for the metal as well as that of the enthalpy change during the removal process.